Recognition, sociability and intolerance: A study of Archibald Campbell (1691–1756). (2nd April 2020) - Stuart-Buttle, Tim
ABSTRACT: The period ca.1650–1800 witnessed a concerted, if neglected debate about the implications of mankind's desire for recognition, which bore directly on discussions of sociability and toleration. Here Thomas Hobbes's writings acted as a powerful stimulus. Hobbes argued that even as the desire for recognition in mankind's natural condition induces individuals to seek society, recognition-seeking generates a mistrust and violence that precludes its realisation. Political authority, allied to the ecclesiastical, is required to constrain men to recognise their mutual obligations to one another: vertical toleration is necessary for horizontal tolerance between individuals to be realisable. The Church of Scotland minister and Professor at St Andrews, Archibald Campbell (1691–1756) offered a comprehensive challenge to Hobbes's interpretation of the relationship between recognition and toleration. Campbell vindicated the desire for esteem from both a moral and a theological perspective: the pursuit of recognition induces us to accommodate our opinions and actions to those of others with whom we live. It gives rise to sociability and mutual fellowship. Yet Campbell accepted that the economy of esteem had been corrupted in 'civilized' societies, and implicated institutional religion in this development. Toleration, he concluded, could not hope to salve the wounds caused by the introduction of intolerance into human relations.